2020
DOI: 10.1186/s40662-020-00207-1
|View full text |Cite
|
Sign up to set email alerts
|

An interferometric ex vivo study of corneal biomechanics under physiologically representative loading, highlighting the role of the limbus in pressure compensation

Abstract: Background: The mechanical properties of the cornea are complex and regionally variable. This paper uses an original method to investigate the biomechanics of the cornea in response to hydrostatic loading over the typical physiological range of intra-ocular pressure (IOP) fluctuations thereby increasing understanding of clinically relevant corneal biomechanical properties and their contributions to the refractive properties of the cornea. Methods: Displacement speckle pattern interferometry (DSPI) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…Previous studies using optical methods also reported a reduced surface tangential strain around the apex during inflation. [12][13][14] Our results expanded upon this observation and confirmed that corneal stroma around the apex indeed stretched minimally under IOP elevation. This may be important for maintaining stable vision during IOP fluctuations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies using optical methods also reported a reduced surface tangential strain around the apex during inflation. [12][13][14] Our results expanded upon this observation and confirmed that corneal stroma around the apex indeed stretched minimally under IOP elevation. This may be important for maintaining stable vision during IOP fluctuations.…”
Section: Discussionsupporting
confidence: 80%
“…Optical imaging was used to quantify corneal surface strains. [12][13][14] Tomographic imaging methods such as optic coherence tomography (OCT) [15][16][17] and high-frequency ultrasound 18,19 have also been applied to characterize corneal deformation under various loads. However, few studies have reported the regional response of the cornea stroma to IOP elevations.…”
Section: Introductionmentioning
confidence: 99%
“…The cornea has a complex and heterogeneous structure resulting in significant spatial and directional variability in mechanical properties. Recent studies [99][100][101] have demonstrated regional variability in mechanical properties of the cornea, especially highlighting differences in the properties of the limbus and peripheral cornea versus the central cornea [101]. These differences are extremely important, and their quantification will be key to the development of customised and targeted treatments for KC.…”
Section: New Technologies Under Development For Clinical Assessment Of Biomechanical Abnormalitymentioning
confidence: 99%
“…Analysis of the distribution of the response is helpful especially when trying to identify localised abnormalities, as the relative deformation in one region can be evaluated relative to the overall deformation of the cornea, removing the reliance on accurate quantification of specific mechanical properties. In fact, it has already been possible to identify similarities in the distribution of the anterior surface displacement of corneas to IOP variations and from this identify corneas that show abnormalities [101,102].…”
Section: New Technologies Under Development For Clinical Assessment Of Biomechanical Abnormalitymentioning
confidence: 99%
See 1 more Smart Citation